Event-triggering load frequency control for multi-area power system based on random dynamic triggering mechanism and two-side closed functional. (February 2023) - Liu, Xingyue; Shi, Kaibo; Ma, Changyou; Tang, Yiqian; Tang, Lin; Wei, Youhua; Han, Yingjun
Abstract: By taking into account sampled-data mechanism and transmission delay, the novel event-triggering load frequency control (LFC) strategy involving random dynamic triggering algorithm (RDTA) is developed for multi-area power systems in this paper. Firstly, an improved multi-area LFC model considering sampling and transmission delay (STD) simultaneously is addressed. Secondly, a modified event-triggering mechanism (ETM) with RDTA is proposed, considering parameter disturbances and a dynamic adjustment mechanism of the triggering threshold. Thirdly, a more advanced Lyapunov–Krasovskii functional (LKF) is constructed, introducing the delay-dependent matrices, more variable cross terms and the two-sided closed functional. Furthermore, two less conservative stability criteria are obtained according to the designed approach. Finally, two multi-area LFC systems are presented to verify the progressiveness of the proposed approach. Highlights: An improved multi-area load frequency control model with sampling and transmission delay is established. A novel event-triggering mechanism with random dynamic triggering algorithm is proposed by considering parameters disturbance and dynamic adjustment mechanism of triggering threshold. A more advanced Lyapunov–Krasovskii functional is constructed by introducing delay dependent matrix, more cross terms of variables and the two-side closed functional.